DIGITAL SUPPLY CHAIN ADOPTION AND CHALLENGES: A TECHNICAL ANALYSIS - Krishna Jayant Baride, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article examines the transformation of traditional supply chains into digital ecosystems, focusing on the implementation challenges, technical foundations, and best practices in the manufacturing sector.The article explores how organizations leverage advanced technologies such as IoT, artificial intelligence, blockchain, and 5G to enhance operational efficiency and supply chain visibility.Through extensive research across multiple industries, the article reveals significant improvements in operational performance, inventory management, and demand forecasting capabilities.The article also addresses critical challenges in system integration, data security, and change management, while providing insights into architectural design principles and risk management frameworks.Furthermore, the article investigates emerging trends in 5G integration, advanced analytics, and cross-industry collaboration, offering valuable perspectives on the future evolution of digital supply chains.